The association of race and COVID-19 mortality. (August 2020) - Golestaneh, Ladan; Neugarten, Joel; Fisher, Molly; Billett, Henny H.; Gil, Morayma Reyes; Johns, Tanya; Yunes, Milagros; Mokrzycki, Michele H.; Coco, Maria; Norris, Keith C.; Perez, Hector R.; Scott, Shani; et al.
Abstract: Background: COVID-19 mortality disproportionately affects the Black population in the United States (US). To explore this association a cohort study was undertaken. Methods: We assembled a cohort of 505, 992 patients receiving ambulatory care at Bronx Montefiore Health System (BMHS) between 1/1/18 and 1/1/20 to evaluate the relative risk of hospitalization and death in two time-periods, the pre-COVID time-period (1/1/20–2/15/20) and COVID time-period (3/1/20–4/15/20). COVID testing, hospitalization and mortality were determined with the Black and Hispanic patient population compared separately to the White population using logistic modeling. Evaluation of the interaction of pre-COVID and COVID time periods and race, with respect to mortality was completed. Findings: A total of 9, 286/505, 992 (1.8%) patients were hospitalized during either or both pre-COVID or COVID periods. Compared to Whites the relative risk of hospitalization of Black patients did not increase in the COVID period (p for interaction=0.12). In the pre- COVID period, compared to Whites, the odds of death for Blacks and Hispanics adjusted for comorbidity was statistically equivalent. In the COVID period compared to Whites the adjusted odds of death for Blacks was 1.6 (95% CI 1.2–2.0, p = 0.001). There was a significant increase in Black mortality risk from pre-COVID to COVID periods (p for interaction=0.02). Adjustment for relevant clinical and social indices attenuated but did not fully explain the observed difference in Black mortality. Interpretation: The BMHS COVID experience demonstrates that Blacks do have a higher mortality with COVID incompletely explained by age, multiple reported comorbidities and available metrics of sociodemographic disparity. Funding: N/A